EFFECT OF HEAT-TREATMENT IN UNDEGRADED PROTEIN PRODUCTION FOR ANIMAL FEED - Rizki Prabowo, Muhammad
Domestic meat and milk production in Indonesia are currently insufficient for the needs of the community. In 2018 there is a deficit of beef fulfillment by 33.7% of the needs and cow's milk by 79.1% of the needs. Various efforts to overcome this problem are underway. Protein is one of the most important components to determine the quality of beef and milk. Approximately 60% of the protein consumed will be degraded in the rumen by microorganisms, hereby reducing the amount of protein absorbed and utilized by livestock. Undegraded protein in animal feed have been proved in reducing protein degradation and increase growth and the amount of milk produced. One method of making undegraded protein is by using heat treatment. The problem that need to be addressed when making undegraded protein by heat treatment is avoiding overprotection that result in a decrease in protein quality. One of the parameters used to determine the quality of protein protection is the protein dispersibility index (PDI). Heated feed will reduce its PDI value which results in increased rumen undegraded protein (RUP). In this research, protein protection was given to soybean meal (SBM) and corn gluten meal (CGM) by using heat temperatures of 70oC, 90oC, dan 110oC with heating time for 20 minutes, 35 minutes, and 50 minutes. The quality of protected proteins was tested by analyzing PDI of the feed on rumen condition (pH 7) and abomasum condition (pH 2) condition. The results of the research showed that the protection on SBM was best produced under 110oC heating conditions for 35 minutes with a PDI value of 14.78% and a RUP value of 85.22%. Protein protection on CGM is insignificant on its value of PDI and its value of RUP. Overprotection does not occur in protected animal feed.